1996
DOI: 10.3758/bf03212421
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving affect from the voice and the face

Abstract: This experiment examines how emotion is perceived by using facial and vocal cues of a speaker. Three levels of facial affect were presented using a computer-generated face. Three levels of vocal affect were obtained by recording the voice of a male amateur actor who spoke a semantically neutral word in different simulated emotional states. These two independent variables were presented to subjects in all possible permutations--visual cues alone, vocal cues alone, and visual and vocal cues together-which gave a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

26
165
2
10

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(203 citation statements)
references
References 30 publications
(35 reference statements)
26
165
2
10
Order By: Relevance
“…It was shown earlier [14] that as compared to emotionally distinct (i.e. happy, angry, sad) facial stimuli, emotionally ambiguous (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…It was shown earlier [14] that as compared to emotionally distinct (i.e. happy, angry, sad) facial stimuli, emotionally ambiguous (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…For example, infant judgments of others' emotions depend on the consistency of others' behavior, such as consistent facial and vocal behavior (Kahana-Kalman & Walker-Andrews, 2001;Walker-Andrews, 1997, 2008. Even after people reach adulthood, behavioral coherence remains important: Adult judgments of facial emotion are strongly disrupted by inconsistent emotional information from other channels of communication (Aviezer et al, 2008;de Gelder & Vroomen, 2000;de Gelder, Bocker, Tuomainen, Hensen, & Vroomen, 1999;Ethofer et al, 2006;Massaro & Egan, 1996;Van den Stock, Grezes, & de Gelder, 2008). In fact, adults often believe that others are being deceptive when the words and nonverbal behaviors of those others are inconsistent (Fleming & Rudman, 1993;Heinrich & Borkenau, 1998;Zuckerman, Driver, & Koestner, 1982).…”
mentioning
confidence: 99%
“…The importance of coherence extends to adulthood. For example, recent research has demonstrated that emotions that are clearly expressed in one channel (e.g., the face) are difficult to interpret when another channel (e.g., the body) presents inconsistent emotional information (Aviezer et al, 2008;de Gelder et al, 1999;de Gelder & Vroomen, 2000;Ethofer et al, 2006;Massaro & Egan, 1996;Van den Stock et al, 2008).…”
mentioning
confidence: 99%
“…In the latter part, we tried to investigate (1) the role of theta oscillations during peaceful mood, (2) the relations of varied modalities with alpha and beta oscillations, respectively, and (3) the increase of gamma oscillations to the audiovisual modality. Besides, although some behavioral studies used dynamic visual and vocal clips of affect expressions and found those more appropriate in real life (Massaro and Egan 1996;Campanella and Belin 2007;Collignon et al 2008), most related psychophysiological and electrophysiological studies have compared static pictures with dynamic sound (Pourtois et al 2002;Koelewijn et al 2010), which have incompatible dimensions. According to that, the present study focused on how inner quiet information is processed in the human brain with both dynamic materials (i.e.…”
Section: Introductionmentioning
confidence: 99%